Efficiency of treatments for controlling Trichoderma spp during spawning in cultivation of lignicolous mushrooms - Colavolpe, María Belén (Braz J Microbiol, 2015)
Trichoderma spp is the cause of the green mold disease in mushroom cultivation production. Many disinfection treatments are commonly applied to lignocellulose substrates to prevent contamination. Mushroom growers are usually worried about the contaminations that may occur after these treatments during handling or spawning. The aim of this paper is to estimate the growth of the green mold Trichoderma sp on lignocellulose substrates after different disinfection treatments to know which of them is more effective to avoid contamination during spawning phase. Three different treatments were assayed: sterilization (121 °C), immersion in hot water (60 and 80 °C), and immersion in alkalinized water. Wheat straw, wheat seeds and Eucalyptus or Populus sawdust were used separately as substrates. After the disinfection treatments, bagged substrates were sprayed with 3 mL of suspension of conidia of Trichoderma sp (10(5) conidia/mL) and then separately spawned with Pleurotus ostreatus or Gymnopilus pampeanus. The growth of Trichoderma sp was evaluated based on a qualitative scale. Trichoderma sp could not grow on non-sterilized substrates. Immersions in hot water treatments and immersion in alkalinized water were also unfavorable treatments for its growth. Co- cultivation with mushrooms favored Trichoderma sp growth. Mushroom cultivation disinfection treatments of lignocellulose substrates influence on the growth of Trichoderma sp when contaminations occur during spawning phase. The immersion in hot water at 60 °C for 30 min or in alkalinized water for 36 h, are treatments which better reduced the contaminations with Trichoderma sp during spawning phase for the cultivation of lignicolous species.